PENGARUH KEBERSYUKURAN TERHADAP SUBJECTIVE WELLBEING PADA MAHASISWA YANG BEKERJA PARUH WAKTU DENGAN SELF EFFICACY SEBAGAI MEDIATOR - Astuti, Astuti; Karos TS, Kiki Andi (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This research was conducted with the aim of knowing the mediating role of Self Efficacy on the relationship between Gratitude and Subjective Wellbeing. The data was taken using an online survey of undergraduate students (S1) of the Department of Elementary School Teacher Education (PGSD) at the University of Muhamadiyah Buton (UMB). The sample in this study was a saturated sample, namely all second semester undergraduate students majoring in PGSD at the University of Muhamadiyah Buton who had a dual status, namely, 50 people who were studying while working. The PROCESS macro from Hayes was used by researchers to analyze the mediation model data. Process Data analysis in this study was carried out using the mediation model on the PROCESS macro from Hayes. The findings in this study indicate that Self Efficacy has a positive and significant role as a mediation on the relationship between Gratitude and Subjective Wellbeing and Gratitude has a positive and significant effect on Subjective Wellbeing.